(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The results of the distribution of bryocommunities in natural vegetation types of the Ukrainian Forest-Steppe are given. The moss vegetation of zonal (broadleaf forests and meadow steppes) vegetation types, extrazonal (pine and oak-pine forests) and azonic vegetation types (marshes, meadows, small deciduous forests, stone, chalky, loessial outcrops) is characterized. The bryofloral features and bryosyntaxonomical differentiation of plant communities that were studied are defined. The characteristics of epigeic, epiphytic, epixylic and epilithic moss vegetation and its affinity to the respective ecotypes are given. 36 associations, 8 subassociations, 22 moss communities of moss vegetation that belongs to 9 classes, 13 orders, 18 alliances are analyzed by the types of vegetation. Their substrate affinity and frequency of occurrence are given.